LESSON STUDY UNTUK MENINGKATKAN MUTU PROSES DAN HASIL PEMBELAJARAN PERKULIAHAN DASAR PEMISAHAN ANALITIK - Sumarni, Woro (Jurnal Inovasi Pendidikan Kimia, 2008)
The research of Lesson Study followed by the observation composed by analyticalÃÂ expertise lecturers was conducted. The aims of this activity are to raise the quality of lessonÃÂ plan ÃÂ produced ÃÂ by ÃÂ the ÃÂ lecturers, ÃÂ the ÃÂ mastering ÃÂ of ÃÂ learning ÃÂ material ÃÂ for ÃÂ each ÃÂ of ÃÂ lecturersÃÂ conducting ÃÂ the Principles ÃÂ of Analytical Separation ÃÂ course, ÃÂ the ÃÂ knowledge ÃÂ of ÃÂ observingÃÂ the ÃÂ learning ÃÂ activity, and motivation ÃÂ of ÃÂ lecturer ÃÂ for ÃÂ self-developments. The responses ofÃÂ lecturers showed that they acquired a good comprehension, particularly on how the studentsÃÂ learning and how lecturers teaching. The others are they got a positive value inside theÃÂ learning process; they had the ability to improve the learning process systematically throughÃÂ collaborative inquiry and they got knowledge from the other lecturers. Thereby, the LessonÃÂ Study activity had to be experienced the benefi t by the analytical expertise lecturers. FromÃÂ the obtained results, it is suggested that the lesson study would be applied continually andÃÂ collaboratively, so we could gain various benefi ts such as collegiality strengthening and theÃÂ reinforcement of daily learning activity related to the long term purposes.Keywords: lesson study; process quality; learning result